2012
DOI: 10.1177/0009922812439621
|View full text |Cite
|
Sign up to set email alerts
|

Attention-Deficit/Hyperactivity Disorder Among Children and Adolescents in the United States

Abstract: Data from the US National Ambulatory Medical Care Survey (NAMCS) for the years 1991 through 2008 were used for this analysis. 23 The US NAMCS is a national probability sample designed and conducted by the US National Center for Health Statistics (NCHS) of the US Centers for Disease Control and Prevention. Data are collected by the US Bureau of the Census. The study is cross-sectional in design. The 3-stage probability sampling procedure, sampling variation, and estimation procedures for the US NAMCS have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 35 publications
2
20
1
Order By: Relevance
“…This argument was also supported by the observation of an increase in new cases diagnosed with ADHD from 2003 to 2009 in the Child Assessment Service under the Hong Kong Department of Health, another statutory body responsible for implementing health care policies (Lau, Liu, & Lee, 2012). Meanwhile, prevalence differences between male and female children were consistent with other studies conducted in the West (Kim, Mutyala, Agiovlasitis, & Fernhall, 2011;Sclar et al, 2012). We showed a narrowing difference in the prevalence of ADHD medication prescribing between the sexes in Hong Kong.…”
Section: Discussionsupporting
confidence: 90%
“…This argument was also supported by the observation of an increase in new cases diagnosed with ADHD from 2003 to 2009 in the Child Assessment Service under the Hong Kong Department of Health, another statutory body responsible for implementing health care policies (Lau, Liu, & Lee, 2012). Meanwhile, prevalence differences between male and female children were consistent with other studies conducted in the West (Kim, Mutyala, Agiovlasitis, & Fernhall, 2011;Sclar et al, 2012). We showed a narrowing difference in the prevalence of ADHD medication prescribing between the sexes in Hong Kong.…”
Section: Discussionsupporting
confidence: 90%
“…Sixty-one percent of the children and adolescents with a clinical diagnosis of ADHD were prescribed one or more of these medications during follow-up. This proportion is lower than in United States samples (Rowland et al 2002;Sclar et al 2012), but is similar to what has been reported in the Scandinavian countries (Zoega et al 2011) and other European countries (Wittchen et al 2011). We also found that 16% of youth with ASD were treated with ADHD medications.…”
Section: Discussionsupporting
confidence: 87%
“…Table 2 reports the temporal prevalence of the diagnosis of ADHD in youth obtained from 12 recent diagnostic reports based on a health care visit or treatment record data. Although age groups differ among the published studies and the surveys vary, the time-trend results reveal consistent diagnostic increases of ADHD across 4 to 17 years that ranged from +11% to 27-fold (Atladottir et al, 2015;Chien, Lin, & Chou, 2012;Garfield et al, 2012;Getahun et al, 2013;Kelwalkar & Nayak, 2010;Olfson, Blanco, Wang, & Laje, 2014;Robison, Skaer, Sklar, & Galin, 2002;Sclar et al, 2012;Toh, 2006;Winterstein et al, 2008;Zito et al, 1999;Zwaanswijk, van Dijk, & Verheij, 2011). Table 3 includes eight teacher-rating reports of the behavioral features common to ADHD in students, comparing ratings separated by 6 to 20 years done under similar classroom circumstances (Achenbach, Dumenci, & Rescorla, 2002;Achenbach & Howell, 1993;de Jong, 1997;Maughan, Collishaw, Melzer, & Goodman, 2008;Sellers, Maughan, Pickles, Thapar, & Collishaw, 2015;Sourander, Niemela, Santalahti, Helenius, & Piha, 2008;Tick, van der Ende, & Verhulst, 2007;Verhulst, van der Ende, & Riebergen, 1997).…”
Section: Methodsmentioning
confidence: 98%